(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
A person creates a material and spiritual world around himself and for himself in forms adapted for perception and development. Therefore, the environment always expresses human relations, captures social shifts and cultural processes in Uzbekistan, it absorbs space as an artistic material, resulting in psychophysical connections between a person and the subject-spatial environment, which is in the process of continuous change.